Do PCAOB Inspections of Foreign Auditors Affect Global Financial Reporting Comparability?* - Ege, Matthew; Kim, Young Hoon; Wang, Dechun (Contemporary Accounting Research, 2021)
ABSTRACT This study investigates whether PCAOB inspections of foreign auditors affect global financial reporting comparability. Foreign auditors may adjust audit methodologies to address PCAOB inspection findings, which could affect financial reporting of local clients. Exploiting both within‐ and cross‐country variation in PCAOB inspections, we predict and find that non‐US‐listed foreign companies' financial reporting becomes more comparable to their US and non‐US industry peers after their auditors undergo an initial inspection. However, there is a decrease in comparability compared to local peers whose auditors have not been inspected. Subsample tests suggest that the improvement in comparability is driven by (i) auditors that satisfactorily address deficiencies and (ii) auditors that do not publicly push back against deficiencies. The effects are dampened after local audit regulators begin inspection programs. Overall, our evidence suggests that the PCAOB international inspection program affects audit methodologies of inspected auditors in a consistent way, improving comparability across jurisdictions. The improved comparability implies that the PCAOB international inspection program may unintentionally help meet accounting regulators' goals of cross‐country financial reporting convergence, which potentially promotes efficient cross‐country capital allocation.